Pengelolaan Modal Sosial Brand Indie Clothing Banjarisme Sebagai Strategi Bertahan - Putra, Ezza Akhan Maulana; Hidayah, Sri (CV. ITTC INDONESIA, 2024)
This research aims to examine the management of social capital in the Banjarisme brand as a survival strategy for Indie Clothing creative businesses. The method used in this research uses a qualitative approach with descriptive research type. Data collection techniques use overt observation, semi-structured in-depth interviews and documentation. This research analysis uses Nan Lin's social capital theory. This research provides an overview of Banjarism's various efforts to utilize their social capital as a strategy to survive in the Indie Clothing industry which often experiences changes in trends and consumer preferences. The results of this research show that: Banjarism invests social capital by actively building and maintaining social networks through regular interactions and participation in the community. They strengthen this network by being involved in various Indie Clothing events in Banjarmasin, maintaining close relationships with other business actors. Through investing in social networks, Banjarism gains access to resources that help them survive in a challenging industry. As well as converting this social capital into profits by opening up other business opportunities. Banjarisme utilizes its distinctive identity inspired by local culture, strengthening its reputation as a representative Indie Clothing brand from Banjarmasin, while ensuring business continuity amidst market dynamics. By having meaning in social capital in the form of appreciation for opportunities and opportunities, encouraging togetherness and trust, and providing social support. The management of social capital carried out by Banjarisme must continue to be maintained and developed in order to maintain the existence of Banjarisme in the Indie Clothing Industry.